Mechanical glass transition revealed by the fracture toughness of metallic glasses - Jittisa Ketkaew (Nature Portfolio, 2018)
Understanding the fracture toughness of metallic glasses remains challenging. Here, the authors show that a fictive temperature controls an abrupt mechanical toughening transition in metallic glasses, and can explain the scatter in previously reported fracture toughness data.